Preparation method of packaging adhesive film layer and flexible perovskite battery
By using a multi-layered encapsulation structure and material co-design, the stability problem of perovskite solar cells in the space environment was solved, achieving high-efficiency high-temperature resistance, radiation resistance, and impact resistance, extending battery life and improving photoelectric conversion efficiency.
Patent Information
- Application Number
- CN202511049993.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-29
- Publication Date
- 2025-10-28
AI Technical Summary
Perovskite solar cells cannot withstand the harsh conditions of high-energy particle radiation, vacuum, temperature alternation, and atomic oxygen in the space environment, resulting in insufficient stability and lifespan.
By employing nano-cerium dioxide shielding, polymer polyimide reinforcement, and synergistic stabilization with compound light stabilizers, and through a multi-layer encapsulation structure design including an encapsulation film layer, a hydrophobic coating, and an anti-reflection protective composite layer, combined with low-temperature lamination and magnetron sputtering deposition technology, a multi-layer encapsulation device is formed, enhancing the battery's airtightness and durability.
It significantly improves the protection performance of perovskite solar cells in extreme environments, extends lifespan and efficiency stability, meets the 25-year service standard for low Earth orbit, has a light transmittance decay of less than 5%, an annual power decay rate of less than 0.5%, and significantly improves resistance to ultraviolet radiation and high and low temperature cycling performance.
Smart Images

Figure CN120843004A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of perovskite battery technology, and relates to a packaging material and battery structure for flexible perovskite batteries, and particularly to a method for preparing a packaging film layer and a flexible perovskite battery. Background Technology
[0002] Perovskite solar cells, as a third-generation novel concept in solar cells, possess advantages such as high photoelectric conversion efficiency, low cost, and flexible fabrication, and have developed rapidly in recent years, with the highest photoelectric conversion efficiency reaching 26.8%. Due to their high efficiency, low cost, and ease of large-scale production, perovskite solar cells have become an important research direction in the photovoltaic field. Furthermore, the tunable bandgap of perovskite materials gives them a significant advantage in spectral absorption, enabling them to absorb light from the visible to near-infrared spectral range. In terms of structural design, perovskite solar cells have evolved from traditional nip mesoporous structures to planar and double perovskite structures to improve efficiency and stability. Simultaneously, significant progress has been made in the development of perovskite / crystalline silicon tandem cells, achieving spectral frequency division by absorbing short-wavelength blue-green light in the perovskite layer and capturing long-wavelength red light in the crystalline silicon layer. In terms of manufacturing processes, the fabrication process of perovskite solar cells is relatively simple, can be carried out at relatively low temperatures, and has low material costs. However, large-area fabrication still faces challenges; the uniformity and defect control of the thin film are key factors affecting efficiency and stability. Furthermore, the stability of perovskite materials remains a major bottleneck for commercial applications, especially under conditions of high temperature, humidity, and light, where perovskite is prone to decomposition.
[0003] With the development of commercial applications of perovskite batteries, the supporting industries for perovskite batteries have also developed. The key to their industrial application lies in battery packaging. The performance and structure of the packaging materials directly affect the overall stability and lifespan of the battery module.
[0004] Utility model patent application number 2023222030460 discloses a perovskite solar cell encapsulation structure, comprising: a lower glass with two grooves; an upper glass with a protrusion on each side, the protrusions interlocking with the grooves, the interlocking points being bonded by laser sintering or adhesive; and a perovskite solar cell module located between the lower and upper glass. By pressing the lower and upper glass together, and then bonding the protrusions with the grooves using laser sintering or adhesive, the lower and upper glass become a single, sealed structure. This also lengthens the path for water and oxygen to enter the encapsulation structure, effectively isolating them and improving its lifespan and performance.
[0005] Utility model patent application number 2023227350408 also discloses a packaging structure for a perovskite solar cell module, which includes a first substrate, a second substrate, a perovskite solar cell located between the first and second substrates, an adhesive film deposited on the surface of the perovskite solar cell, and an encapsulation layer disposed around the perovskite solar cell. The encapsulation layer covers the entire cross-section of the adhesive film, at least a portion of the cross-section of the first substrate, and at least a portion of the cross-section of the second substrate. By sealing the first substrate, the second substrate, and the adhesive film through the encapsulation layer, the path for external moisture and oxygen to permeate is lengthened, increasing the difficulty of external moisture and oxygen permeation and improving airtightness.
[0006] Utility model patent application number 2024204855559 also discloses a packaging structure for a perovskite solar cell, which includes a substrate, a transparent conductive film layer, a perovskite functional layer, and a packaging component stacked sequentially from bottom to top. The packaging component includes a packaging cover plate, a first encapsulating film, and a second encapsulating film. A sealed space is formed between the substrate and the packaging cover plate through the second encapsulating film, enabling the sealed packaging of the transparent conductive film layer and the perovskite functional layer. The first encapsulating film is located between the perovskite functional layer and the packaging cover plate to fix the perovskite functional layer. By effectively sealing the transparent conductive film layer and the perovskite functional layer, it isolates them from the external air environment, preventing air, moisture, and other substances from entering between the substrate and the packaging cover plate and affecting the transparent conductive film layer and the perovskite functional layer. This avoids the decomposition of the battery's functional materials, which would affect battery performance, enabling the battery to be used stably for a long time and improving its lifespan and stability.
[0007] Most of the perovskite batteries mentioned above are used on the Earth's surface. However, in aerospace and other outer space scenarios, due to the special environment of high-energy particle radiation, atomic oxygen, and temperature alternation, it is necessary to break through the limitations of ground-based packaging and improve the battery's high-temperature resistance, radiation resistance, and impact resistance in the space environment to adapt to the harsh conditions of radiation, vacuum, temperature alternation, and atomic oxygen in the space environment. Summary of the Invention
[0008] The purpose of this invention is to solve the technical problem that perovskite batteries in the prior art are limited by the fact that the materials cannot be used in the harsh conditions of space environment such as irradiation, vacuum, temperature alternation, and atomic oxygen. The invention provides a method for preparing an encapsulation film layer and a flexible perovskite battery. Through the design of materials and device encapsulation structure, the excellent airtightness of the battery is improved, effectively blocking the intrusion of external water and oxygen, and ensuring the stability of the perovskite battery in special environments.
[0009] A method for preparing an encapsulating film layer includes the following steps: Step S1: Matrix pretreatment and condensation reaction; Under nitrogen protection, the POE matrix material was heated to 75-85℃ to melt, nano-cerium dioxide composite was added, and stirred at 500 rpm for 30 minutes; a compound initiator was added, and the mixture was mixed at a temperature controlled ≤40℃; finally, 1-3 wt% polyimide prepolymer was added, and the mixture was reacted at 110℃ for 1 hour. Step S2: Antioxidant dispersion and curing; Add antioxidant masterbatch to the product of step S1, heat to 130°C and stir at 300 rpm for 20 minutes, then cure at 0.5 MPa pressure for 2 hours to obtain a film. Step S3: Ultraviolet stabilization treatment; Add a compound light stabilizer to the cured adhesive film in step S2, melt-blend it at 170°C using a twin-screw extruder, extrude and granulate it, and then calender it into a film to obtain the encapsulating adhesive film layer.
[0010] Further, in step S1, the nano-cerium dioxide composite is prepared by silanizing 0.3-0.5 wt% nano-cerium dioxide with 0.5-1.5 wt% aminosilane coupling agent; The compound initiator is an acetone solution containing 0.5-1.0 wt% tert-butylperoxycarbonate-2-ethylhexyl ester and 0.1-0.3 wt% tert-pentyl peroxyacetate.
[0011] Further, in step S2, the antioxidant masterbatch is prepared by dispersing 0.2 wt% pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] on a POE carrier.
[0012] Further, in step S3, the compound light stabilizer includes 0.2 wt% UV-531 and 0.1 wt% hindered amine light stabilizer HALS-622.
[0013] A flexible perovskite solar cell includes: a radiation cooling coating, a solar panel substrate, an adhesive damping layer, and a perovskite encapsulation structure arranged sequentially. The perovskite encapsulation structure includes a top encapsulation layer, an encapsulation film layer, a perovskite module, a substrate layer, an anti-reflective protective composite layer, and a hydrophobic coating arranged sequentially. The hydrophobic coating and the anti-reflective protective composite layer encapsulate the top encapsulation layer, the encapsulation film layer, the perovskite module, and the substrate layer. The encapsulation film layer and the substrate layer encapsulate the perovskite module. The encapsulating film layer is prepared by the encapsulating film layer preparation method described above.
[0014] Furthermore, the perovskite assembly includes a metal electrode layer, an electron transport layer, a perovskite layer, a hole transport layer, and a transparent electrode layer arranged sequentially.
[0015] Furthermore, the anti-reflective protective composite layer includes an inner silicone coating and an outer MgF2 / SiO2 layer. The thickness of the silicone coating is 5±2μm, and the thickness of the MgF2 / SiO2 layer is 120-130nm. The substrate is a CPI layer or radiation-resistant glass with a thickness of 70-90 μm; The top encapsulation layer is a CPI layer or radiation-resistant glass with a thickness of 50-80μm; The hydrophobic coating is made of fluorinated acrylic nano-coating with a thickness of 5-15μm; The adhesive damping layer is made of thermally conductive silicone and has a thickness of 200-300μm. The material of the radiation cooling coating is an inorganic ceramic coating, a metal oxide coating, or a polymer-based composite coating, with a thickness of 100-300μm; The solar panel substrate is made of glass fiber or carbon fiber, with a thickness of 25-125um.
[0016] Furthermore, the anti-reflection protective composite layer is deposited on the substrate layer by magnetron sputtering deposition. During magnetron sputtering deposition, the vacuum level of the magnetron sputtering equipment is less than 5 × 10⁻⁶. -4 Pa, sputtering power 100-180W, sputtering time 3-5min, working pressure below 2Pa, argon flow rate 50-100sccm, annealing temperature 200-300℃, annealing time 30min.
[0017] Furthermore, the anti-reflective protective composite layer is coated with an organosilicon coating on the surface of the MgF2 / SiO2 layer by scraping or slot coating. The silicone coating is made of fluorinated silicone resin.
[0018] Furthermore, the top encapsulation layer and the encapsulating film layer are connected by low-temperature lamination; Before low-temperature lamination, laser-drilled holes are made around the encapsulation film layer, and the perovskite component is electrically connected to conductive tin, with the other end of the conductive tin protruding through the laser-drilled holes.
[0019] The beneficial effects of this invention are as follows: 1. In this invention, when preparing the encapsulating film layer, nano-cerium dioxide shielding, polymer polyimide reinforcement, compound light stabilizer synergistic stabilization, and gradient curing are innovatively adopted. The perovskite solar cell prepared in this way has doubled its lifespan and extended its failure cycle under ultraviolet / humid heat / irradiation by more than 2 times; efficiency stability is improved, light transmittance decay is ≤5%, and the annual power decay rate of the module is <0.5%; space adaptability is improved, meeting the 25-year service standard for low Earth orbit.
[0020] 2. In this invention, the perovskite battery exhibits significantly improved protective performance under extreme environments. Specifically, it demonstrates strong resistance to ultraviolet radiation, with a transmittance decrease of ≤5% after 96 hours of ultraviolet aging and a yellowing index ΔYI ≤2 (compared to ΔYI > 5 for traditional films); it is resistant to high and low temperature cycling, with the polyimide prepolymer forming an interpenetrating network to enhance thermal stability (glass transition temperature Tg > 300℃), and the gradient curing of the compounded initiator reducing internal stress and preventing thermal cycling cracking; it is resistant to space irradiation and atomic oxygen erosion, with CeO2 capturing free radicals to reduce reactive oxygen species (ROS) generated by charged particle irradiation, and the polyimide PI segments enhancing resistance to γ / X-ray damage (transmittance retention > 95% after irradiation).
[0021] 3. In this invention, the perovskite battery lifespan and efficiency are guaranteed by improved water and oxygen barrier properties. Silanized CeO2 fills the gaps between POE molecules, extending the water vapor permeation path (reducing WVTR by 40%), and the PI-POE crosslinking network inhibits gas diffusion (O2 transmittance <0.5cm³ / m²·day). After 96 hours of accelerated aging, the battery transmittance is ≥91% (initial value 96%), ensuring that the battery's photoelectric conversion efficiency decays by ≤1%. Aminosilane-modified CeO2 neutralizes acidic ions, reducing Na⁺ migration (leakage current <10). -8 A / cm²).
[0022] 4. In the flexible perovskite battery of the present invention, the perovskite module is first covered by an encapsulating film layer and a substrate layer, and then covered by a hydrophobic coating and an anti-reflective protective composite layer. Through the design and innovation of the materials of each component of the flexible perovskite battery and the device encapsulation structure, the excellent airtightness of the battery is significantly improved, effectively blocking the intrusion of external water and oxygen, ensuring the stability of the perovskite battery in special environments. The battery has better high temperature resistance, radiation resistance and impact resistance in the space environment, and can adapt to the harsh conditions of space environment such as radiation, vacuum, temperature alternation and atomic oxygen.
[0023] 5. In this invention, the organosilicon coating uses fluorinated organosilicon resin with a thickness of 3-7 μm. Through optimized structural design, a double-layer composite method is used to improve light absorption efficiency while composited with a protective layer that is resistant to scratches, space dust erosion and antigenic oxygen erosion, thereby achieving synergistic enhancement of optical performance and environmental tolerance.
[0024] 6. In this invention, the multilayer composite encapsulation device uses multilayer encapsulation on both the top and bottom, and the adhesive film layer, hydrophobic coating, and silicone coating can all serve as water and oxygen barrier layers.
[0025] 7. In this invention, micropores are pre-set around the adhesive film layer and the top encapsulation layer during lamination and encapsulation, so that the conductive solder strip is partially exposed. That is, the conductive solder strip is bonded to the battery metal electrode through conductive silver paste doped with carbon nanotubes to form a low-resistance connection, which facilitates battery structural performance testing and subsequent modular series connection.
[0026] 8. In this invention, the encapsulation layer is stacked in the order of "top encapsulation layer - encapsulating film layer - battery device" and laminated and melted under conditions of 80-90℃ and 0.5-1MPa, which can avoid damage to the active layer of the perovskite battery by high temperature and high pressure.
[0027] 9. In this invention, by “layered functionalization + multi-environment synergy”, the limitations of traditional packaging that only focuses on water and oxygen barrier are broken, providing a structured solution for the application of perovskite batteries in harsh environments such as space and high altitude. Attached Figure Description
[0028] Figure 1 This is a schematic diagram of the structure of the present invention; Figure 2 This is in the present invention; The attached figures are labeled as follows: 1-Radiative cooling coating, 2-Solar wing substrate, 3-Adhesive damping layer, 4-Perovskite encapsulation structure, 41-Hydrophobic coating, 42-Top encapsulation layer, 43-Encapsulation film layer, 44-Perovskite component, 45-Base layer, 46-Antireflective protective composite layer, 441-Metal electrode layer, 442-Electron transport layer, 443-Perovskite layer, 444-Hole transport layer, 445-Transparent electrode layer. Detailed Implementation
[0029] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments.
[0030] Therefore, all other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0031] Example 1 This embodiment provides a method for preparing an encapsulating film layer. The encapsulating film layer prepared by this method can be applied to flexible perovskite solar cells to improve the performance of flexible perovskite solar cells.
[0032] Taking the small-batch preparation of the encapsulating film layer in the laboratory as an example (for large-batch preparation, simply scale up the application amount proportionally), the specific preparation steps are as follows: Step S1: Matrix pretreatment and condensation reaction; Under nitrogen protection, 100g of POE matrix material was heated to 75-85℃ to melt, and 1.4g of nano-cerium dioxide composite (comprising nano-cerium dioxide (0.4g by weight, concentration 0.3-0.5wt%) and aminosilane coupling agent (1.0g by weight, concentration 0.5-1.5wt%), both prepared by silanization modification) was added, and the mixture was stirred at 500rpm for 30 minutes. Then, 4.95g of a compound initiator (an acetone solution containing 0.5-1.0wt% tert-butylperoxycarbonate-2-ethylhexyl ester and 0.1-0.3wt% tert-butylperoxycarbonate-2-ethylhexyl ester, wherein tert-butylperoxycarbonate-2-ethylhexyl ester is added) was added. The following mixtures were prepared: 0.75 g of ethylhexyl ester, 0.2 g of pentyl peroxypentate, and 4 g of acetone. The mixture was then stirred at a temperature ≤40℃. Finally, 2 g of polyimide prepolymer (1-3 wt%) was added, and the mixture was reacted at 110℃ for 1 hour.
[0033] By adding a polyimide prepolymer (such as PI prepolymer, which is formed by prepolymerization of ODPA / ODA monomers in NMP with a solid content of 30%), a condensation reaction is carried out with the amine groups of the silane coupling agent, thereby achieving the grafting of PI prepolymer onto the POE molecular chain.
[0034] Step S2: Antioxidant dispersion and curing; Add 10g of antioxidant masterbatch to the product of step S1, heat to 130℃ and stir at 300rpm for 20 minutes, then cure at 0.5MPa pressure for 2 hours to obtain the adhesive film.
[0035] The antioxidant masterbatch was prepared by pre-dispersing 0.2 wt% pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] on a POE carrier.
[0036] Step S3: Ultraviolet stabilization treatment; Add 0.3g of compound light stabilizer to the cured adhesive film in step S2, melt-blend it at 170℃ using a twin-screw extruder, extrude and granulate it, and then calender it into a film to obtain the encapsulation adhesive film layer.
[0037] The compound light stabilizers include UV-531 (0.2g by weight, 0.2wt%) and hindered amine light stabilizer HALS-622 (0.1g by weight, 0.1wt%).
[0038] Example 2 This embodiment provides a flexible perovskite battery that is suitable for harsh space environments such as irradiation, vacuum, temperature alternation, and atomic oxygen.
[0039] like Figure 1As shown, the flexible perovskite solar cell includes, from top to bottom, a radiation cooling coating 1, a solar panel substrate 2, an adhesive damping layer 3, and a perovskite encapsulation structure 4.
[0040] The perovskite encapsulation structure 4 includes, from top to bottom, a top encapsulation layer 42, an encapsulation film layer 43, a perovskite component 44, a base layer 45, an anti-reflective composite layer 46, and a hydrophobic coating 41. The hydrophobic coating 41 has a top surface, four sides, and a bottom opening. The hydrophobic coating 41, together with the bottom anti-reflective composite layer 46, encapsulates the top encapsulation layer 42, the encapsulation film layer 43, the perovskite component 44, and the base layer 45 within the cavity formed by the hydrophobic coating 41 and the anti-reflective composite layer 46. The bottom surface of the encapsulation film layer 43 has a groove. The encapsulation film layer 43 and the base layer 45 encapsulate the perovskite component 44 within the cavity formed by the groove on the bottom surface of the encapsulation film layer 43 and the base layer 45.
[0041] The encapsulating film layer 43 is prepared by the encapsulating film layer preparation method described in Example 1.
[0042] like Figure 2 As shown, the perovskite component 44 includes: a transparent electrode layer 445, a hole transport layer 444, a perovskite layer 443 (core light-absorbing layer), an electron transport layer 442, and a metal electrode layer 441 arranged sequentially from bottom to top (relative to the electrode layer above the substrate). These electrode layers are surrounded by a hydrophobic coating (10±5μm thick) to reduce moisture adsorption and protect the perovskite layer from water and oxygen erosion.
[0043] The anti-reflection protective composite layer 46 adopts a double-layer structure (silicone coating + MgF2 / SiO2 film), utilizing the double-layer anti-reflection principle to simultaneously provide protection against atomic oxygen. The inner silicone coating is 5±2μm thick, and the outer MgF2 / SiO2 layer is 120-130nm thick (here, MgF2 / SiO2 layer refers to either the MgF2 layer or the SiO2 layer). This layer reduces incident light reflection, improves incident light utilization, and also protects against atomic oxygen corrosion in the space environment.
[0044] The substrate 45 is made of CPI (transparent polyimide) or flexible radiation-resistant glass, with a thickness of 70-90 μm. Compared to a rigid substrate, it can significantly reduce weight, lower spacecraft launch costs, provide structural support, possess excellent flexibility, and resist high-energy particle radiation, making it suitable for the space environment.
[0045] The encapsulating film layer 43 is prepared using the method described in Example 1, and its thickness is 100-200 μm. It can serve as a sealant and adhesive, isolate water and oxygen, and also has a certain degree of flexibility to adapt to structural stress.
[0046] The top encapsulation layer 42 is a CPI layer or radiation-resistant glass with a thickness of 50-80 μm. It further strengthens the encapsulation, protects the internal structure, and maintains light transmittance.
[0047] The hydrophobic coating 41 is made of fluorinated acrylic nano-coating with a thickness of 5-15μm. Before launch, spacecraft equipment needs to be placed in the ground environment for 3-6 months to undergo various detailed inspections. Compared with the space environment, the ground environment has serious water and oxygen corrosion problems. The perovskite functional layer has hydrophobic coatings on both sides, providing all-round protection against water and oxygen.
[0048] The adhesive damping layer 3 is made of thermally conductive silicone and has a thickness of 200-300μm. It serves two purposes: bonding the upper structure, conducting heat to the substrate, and providing damping and cushioning to cope with the vibration and thermal expansion and contraction stress of the spacecraft.
[0049] The radiation cooling coating 1 is made of inorganic ceramic coating, metal oxide coating, or polymer-based composite coating, with a thickness of 100-300μm. It utilizes the principle of radiation cooling to dissipate heat into outer space in the form of infrared radiation, thereby reducing the battery's operating temperature and improving stability (heat dissipation is important in the space environment because convection cooling is difficult in a vacuum, and radiation cooling is an effective means).
[0050] The solar panel substrate 2 is made of glass fiber substrate or carbon fiber substrate, with a thickness of 25-125. Considering the weight and cost issues of spacecraft launch, this solar panel substrate, in addition to providing overall structural support, also features lightweight and high strength, making it suitable for the weight reduction requirements of aerospace applications, while also possessing certain mechanical properties.
[0051] Each of the above layers has a specific function, such as anti-reflection, anti-radiation, heat conduction, shock absorption, and cooling, which work together to improve the stability and lifespan of the battery in the space environment.
[0052] The top encapsulation layer 42 and both sides of the encapsulation structure are coated with a fluorinated acrylic nano-coating as a hydrophobic coating. The coating method can be either dip coating or spray coating.
[0053] The hydrophobic coating 41 and the solar panel substrate 1 are coated with silicone rubber material using an adhesive dispensing device. By controlling parameters such as the amount of adhesive output, dispensing speed, and pressure, the adhesion between the overall encapsulation structure and the substrate is increased.
[0054] The anti-reflection protective composite layer 46 is deposited on the substrate layer 45 by magnetron sputtering deposition. During magnetron sputtering deposition, the vacuum level of the magnetron sputtering equipment is less than 5 × 10⁻⁶. -4 Pa, sputtering power 100-180W, sputtering time 3-5min, working pressure below 2Pa, argon flow rate 50-100sccm, annealing temperature 200-300℃, annealing time 30min.
[0055] In the anti-reflective protective composite layer 46, an organosilicon coating is applied to the surface of the MgF2 / SiO2 layer by scraping or slit coating; the organosilicon coating is a fluorinated organosilicon resin.
[0056] A perovskite battery structure is fabricated on a battery substrate, with tin-plated copper foil attached above the metal electrode area as conductive leads. Specifically, the top encapsulation layer 42 and the encapsulating film layer 43 are connected via low-temperature lamination. Before low-temperature lamination, laser-drilled vias are made around the encapsulating film layer 43, and the perovskite module 44 is electrically connected to conductive tin, with the other end of the conductive tin extending through the laser-drilled via. Before the low-temperature lamination of the encapsulating film layer and the top encapsulation layer, internal holes (0.5-1 mm in diameter) are drilled around the perimeter using a laser to expose the conductive tin strips and connect them to external circuitry for battery performance testing.
[0057] Example 3 This embodiment further illustrates the application scenarios of this battery, which can be used in spacecraft and ground-based photovoltaic systems. Specifically: For aerospace solar array applications, the packaging structure is designed around the collaborative design of "optical enhancement + water and oxygen barrier + thermal management + mechanical protection". Through the stacking of multiple functional film layers, it adapts to the harsh conditions of space environment such as irradiation, vacuum, temperature alternation, and atomic oxygen, ensuring the photoelectric conversion efficiency and long-term stability of perovskite solar cells.
[0058] To address the challenges posed by high-energy particle radiation, atomic oxygen, and temperature fluctuations in space, a radiation-resistant substrate, an organosilicon atomic oxygen protection layer, and a radiation cooling layer work together to overcome the limitations of ground-based packaging.
[0059] 1. The coordinated effect of multiple layers above and below: (1) "Double protection against water and oxygen": The hydrophobic coating wraps the perovskite functional area on both sides and the encapsulation film layer seals it, blocking water and oxygen intrusion in all dimensions; (2) Antireflection layer + radiation cooling layer: can achieve "maximum light utilization + minimum heat accumulation", improving photoelectric conversion efficiency and stability; (3) Mechanical and thermal integration: The adhesive damping layer thermal grease simultaneously achieves thermal conduction and damping functions, solving the dual needs of vibration dynamics and thermal management in aerospace scenarios; (4) Radiation resistance: Both the base layer and the top encapsulation layer are made of CPI / radiation-resistant glass to resist ionizing radiation from space; (5) Atomic oxygen protection: The silicone coating of the anti-reflective composite layer is used to resist low-orbit atomic oxygen corrosion.
[0060] 2. Application Scenarios Demonstration Spacecraft scenario: Spacecraft solar panels, adapted to extreme conditions such as space radiation, vacuum, and temperature fluctuations; Ground-mounted photovoltaic scenarios: Ground-mounted photovoltaic systems have reduced radiation resistance design and utilize radiation cooling layers to reduce temperature rise and improve power generation efficiency.
[0061] Because the structure of this invention is adapted to the space environment, it can be directly applied to the solar panels of spacecraft. If the design for radiation resistance and atomic oxygen protection is adjusted, such as by weakening the relevant layers, it can also be used in ground-based photovoltaic power stations to reduce temperature rise and improve power generation efficiency through radiative cooling.
Claims
1. A method for preparing an encapsulating film layer, characterized in that, Includes the following steps: Step S1: Matrix pretreatment and condensation reaction; Under nitrogen protection, the POE matrix material was heated to 75-85℃ to melt, nano-cerium dioxide composite was added, and stirred at 500 rpm for 30 minutes; a compound initiator was added, and the mixture was mixed at a temperature controlled ≤40℃; finally, 1-3 wt% polyimide prepolymer was added, and the mixture was reacted at 110℃ for 1 hour. Step S2: Antioxidant dispersion and curing; Add antioxidant masterbatch to the product of step S1, heat to 130°C and stir at 300 rpm for 20 minutes, then cure at 0.5 MPa pressure for 2 hours to obtain a film. Step S3: Ultraviolet stabilization treatment; Add a compound light stabilizer to the cured film after step S2, melt-blend it at 170°C using a twin-screw extruder, extrude and granulate it, and then calender it into a film.
2. The method for preparing an encapsulating film layer as described in claim 1, characterized in that: In step S1, the nano-cerium dioxide composite is prepared by silanizing 0.3-0.5 wt% nano-cerium dioxide with 0.5-1.5 wt% aminosilane coupling agent; The compound initiator is an acetone solution containing 0.5-1.0 wt% tert-butylperoxycarbonate-2-ethylhexyl ester and 0.1-0.3 wt% tert-pentyl peroxyacetate.
3. The method for preparing an encapsulating film layer as described in claim 1, characterized in that: In step S2, the antioxidant masterbatch is prepared by dispersing 0.2 wt% pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid] on a POE carrier.
4. The method for preparing an encapsulating film layer as described in claim 1, characterized in that: In step S3, the compound light stabilizer includes 0.2 wt% UV-531 and 0.1 wt% hindered amine light stabilizer HALS-622.
5. A flexible perovskite solar cell, characterized in that, include: The radiation cooling coating (1), solar wing substrate (2), adhesive damping layer (3) and perovskite encapsulation structure (4) are arranged sequentially. The perovskite encapsulation structure (4) includes a top encapsulation layer (42), an encapsulation film layer (43), a perovskite module (44), a substrate layer (45), an anti-reflection protection composite layer (46), and a hydrophobic coating (41) arranged sequentially. The hydrophobic coating (41) and the anti-reflection protection composite layer (46) encapsulate the top encapsulation layer (42), the encapsulation film layer (43), the perovskite module (44), and the substrate layer (45). The encapsulation film layer (43) and the substrate layer (45) encapsulate the perovskite module (44). The encapsulating film layer (43) is prepared by the encapsulating film layer preparation method according to any one of claims 1-4.
6. A flexible perovskite solar cell as described in claim 5, characterized in that, The perovskite assembly (44) includes a metal electrode layer (441), an electron transport layer (442), a perovskite layer (443), a hole transport layer (444), and a transparent electrode layer (445) arranged sequentially.
7. A flexible perovskite solar cell as described in claim 5, characterized in that, The anti-reflective protective composite layer (46) includes an inner silicone coating and an outer MgF2 / SiO2 layer. The thickness of the silicone coating is 5±2μm and the thickness of the MgF2 / SiO2 layer is 120-130nm. The substrate (45) is a CPI layer or radiation-resistant glass with a thickness of 70-90 μm; The top encapsulation layer (42) is a CPI layer or radiation-resistant glass with a thickness of 50-80 μm; The hydrophobic coating (41) is made of fluorinated acrylic nano-coating with a thickness of 5-15 μm; The adhesive damping layer (3) is made of thermally conductive silicone with a thickness of 200-300μm; The material of the radiation cooling coating (1) is an inorganic ceramic coating, a metal oxide coating or a polymer-based composite coating, with a thickness of 100-300 μm; The solar panel substrate (2) is made of glass fiber or carbon fiber with a thickness of 25-125um.
8. A flexible perovskite solar cell as described in claim 7, characterized in that, The anti-reflection protective composite layer (46) is deposited on the substrate layer (45) by magnetron sputtering deposition. During magnetron sputtering deposition, the vacuum level of the magnetron sputtering equipment is less than 5 × 10⁻⁶. -4 Pa, sputtering power 100-180W, sputtering time 3-5min, working pressure below 2Pa, argon flow rate 50-100sccm, annealing temperature 200-300℃, annealing time 30min.
9. A flexible perovskite solar cell as described in claim 7, characterized in that, In the anti-reflection protective composite layer (46), an organosilicon coating is applied to the surface of the MgF2 / SiO2 layer by scraping or slit coating. The silicone coating is made of fluorinated silicone resin.
10. A flexible perovskite solar cell as described in claim 7, characterized in that, The top encapsulation layer (42) and the encapsulation film layer (43) are connected by low-temperature lamination; Before low-temperature lamination, laser through holes are opened around the encapsulation film layer (43) by laser drilling, and the perovskite component (44) is electrically connected to the conductive tin, with the other end of the conductive tin passing through the laser through hole.
Citation Information
Patent Citations
White EVA adhesive film for photovoltaic module encapsulation
CN104745109A
Packaging adhesive film, preparation method thereof and photovoltaic module
CN118146735A